2003
DOI: 10.1097/01.cpm.0000087525.38267.23
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Life-Threatening Hemoptysis

Abstract: The classic concept of massive hemoptysis has been replaced by the newer one of life-threatening hemoptysis (LTH), which means any bleeding from the lower respiratory tract that may cause the death of the patient. Although asphyxia is the usual mechanism of death, hypovolemic shock also plays a role in certain cases. The amount of expectorated blood does not always correlate with the actual volume of bleeding. The underlying state of health, especially basal respiratory function, plays a crucial role when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
1
0
2
Order By: Relevance
“…21,22 Life-threatening hemoptysis and massive alveolar hemorrhage should be treated according to the specific cause of bleeding. 23 Diffuse alveolar hemorrhage after bone marrow transplant may respond to the infusion of recombinant factor VIIa. 24 It has been suggested that the use of amiodarone to treat cardiac dysrhythmias in patients under chemotherapy could enhance potential chemotherapy-induced lung toxicity.…”
Section: Treatmentmentioning
confidence: 99%
“…21,22 Life-threatening hemoptysis and massive alveolar hemorrhage should be treated according to the specific cause of bleeding. 23 Diffuse alveolar hemorrhage after bone marrow transplant may respond to the infusion of recombinant factor VIIa. 24 It has been suggested that the use of amiodarone to treat cardiac dysrhythmias in patients under chemotherapy could enhance potential chemotherapy-induced lung toxicity.…”
Section: Treatmentmentioning
confidence: 99%
“…La realizació n de este procedimiento no es posible en el 5-10% de los casos (imposibilidad de cateterizar todas las arterias, inestabilidad del caté ter o riesgo de ocluir una colateral no bronquial) y no debería considerarse como una solució n definitiva aunque mejore los resultados conseguidos por la fibrobroncoscopia en el control del sangrado 25,26 . Es aplicable en la fase má s aguda y hasta poner en marcha un tratamiento mé dico o quirú rgico má s definitivo, aunque puede realizarse con una intenció n má s definitiva ante la imposibilidad o el fracaso de estos ú ltimos 27,28 .…”
unclassified
“…Su reconocida utilidad y amplia implantació n recogida en mú ltiples estudios publicados en la literatura mé dica estos ú ltimos añ os no se acompañ a de un conocimiento amplio de la evolució n de estos pacientes a largo plazo. El resangrado tras la embolizació n es inferior al de la fibrobroncoscopia y atribuible a una embolizació n incompleta, revascularizació n o recanalizació n de la arteria asociada a una dificultad de control de la enfermedad de base 25,26 . El resangrado tras la embolizació n es inferior al de la fibrobroncoscopia y atribuible a una embolizació n incompleta, revascularizació n o recanalizació n de la arteria asociada a una dificultad de control de la enfermedad de base 25,26 .…”
unclassified